APPLICATIVE CONSTRUCTIONS IN MALANG JAVANESE - Ayu Lityaningrum (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Malang Javanese has special characteristics due to many migrants in Malang that can affect the use of the Javanese language. Since many mother tongues of different places are spoken there, Malang Javanese can be expected to show divergences from the Standard Javanese seen in applicative constructions. This research aimed to identify and describe the applicative marker and formulate its tendency. A qualitative approach was used to gain a deeper result. The data were taken from Twitter in the form of intransitive, transitive, and ditransitive sentences. Then, the data were collected using copy-paste technique and processed using AntConc so that all sentences containing the applicative marker must be collected. The theories applied were grammatical roles by Palmer, applicative constructions by Peterson, and Javanese grammar. The research result showed that the applicative constructions in Malang Javanese were in the form of suffix -no and -i. The roles of the suffix -no were used to promote benefactive and locative obliques to the core argument. Next, the role of the suffix -i was to promote benefactive recipients oblique to the core argument. An interesting finding showed an unusual pattern of the applicative construction that had no suffix marking or no-applicative marking. The use of the suffix -no and the suffix -i were not always categorized as applicative markers. By comparing the applicative constructions in Standard Javanese, it was found the same roles for each suffix.